Optimizing Management Information Systems Based on Efficiency and Quality Management - Eka Putra (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this research is to explore the increase in efficiency and quality of management in optimizing the application of management information systems at MAN 1 Sungai Full. This research uses qualitative research, and data collection techniques through observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and data verification. The results of this study indicate that the management of optimizing the implementation of management information systems at MAN 1 Sungai Penuh collects data containing teacher and staff data to manage important information about teaching staff and staff registered at the school such as biodata, rank, position, address, working status, hours work history, educational history, career history, training history, attendance rate, salary info and others, management information systems related to student services in the form of New Student Admissions data, student biodata, Management of Student Class Promotion (manual or automatic), Graduation Management / Alumni, Printing Student Cards, and Management of Student Discipline, and information systems related to teaching and learning activities such as Information Systems containing Curriculum Management, Scheduling of Teaching Units, Management of Student Academic Grades and reports on Student Study results, and Student Presence in teaching and learning activities.